Calibrated Comparison of the Seismic Behavior of Masonry Walls with King Kong Bricks vs. Tambourine Bricks Using Nonlinear Simulation In ETABS - Lenin Bendezú, R. (2025)
In Lima, the informal construction of confined masonry walls with non-standard materials, such as King Kong bricks, is a widespread practice that raises concerns regarding seismic safety. This study presents a calibrated numerical comparison between two full-scale confined masonry walls with identical geometry: one constructed with standardized King Kong bricks and the other with King Kong bricks, commonly used in informal buildings. Both walls were modeled in ETABS 22 using a pivot hysteresis model, calibrated with experimental results from cyclic tests. Nonlinear static analyses were performed under increasing reversible lateral loads. Key seismic performance indicators were extracted from the simulated hysteresis curves : initial lateral stiffness, maximum shear capacity, strength and strain ductility, and accumulated dissipated energy. The results indicate that the King Kong brick wall exhibited greater stiffness, higher shear strength, and better energy dissipation capacity compared to the tambourine brick wall. The latter showed early stiffness degradation, low energy absorption, and lower ductility, reflecting poor seismic performance. The study highlights the influence of brick type on structural performance and demonstrates the usefulness of calibrated ETABS simulations as an accessible and effective tool for assessing the nonlinear behavior of confined masonry walls in contexts where experimental testing is unavailable. The findings support the need to raise regulatory awareness and promote structural interventions in informal construction areas.